Synthesis of 2,2,4-Trimethyl-2,3-dihydro-1H-1,5-benzodiazepine using Treated Natural Zeolite Catalyst - Maulidan Firdaus; Meyta Dyah Prameswari (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2019)
The cyclocondensation of 1,2-phenylenediamine and acetone in the presence of treated natural zeolite catalyst (TNZ) under solvent-free condition has been done. The research consisted of three steps. The first step was treatment of natural zeolite by mixing this material in hydrochloric acid solution at 50 °C for 1 hour to be followed by soaking the zeolite in ammonium chloride solution for 5 days. The second step was solvent-free condensation of 1,2-phenylenediamine and acetone using TNZ at 50 °C for 2 hours with weight ratio variation of catalyst, i.e. 15, 30, 45, and 60% (wt/wt). The third step was to study catalyst reusability for the condensation reaction. Based on TLC, FTIR, and 1H NMR analyses, the condensation afforded 2,2,4-trimethyl-2,3-dihydro-1H-1,5-benzodiazepine as the product in 73% yield with the optimum of catalyst loading at 30% (wt/wt). The reusability test showed that the catalyst can be reused for the cyclocondensation for four times.